2019
DOI: 10.7759/cureus.5072
|View full text |Cite
|
Sign up to set email alerts
|

Personality Dynamism and Academic Performance Among Boarders and Non-boarders Studying in a Medical University

Abstract: Introduction The personality of a human being consists of his behavior, cognition, emotional abilities, and interaction with his surroundings. The personality of an individual is modified by his ability for social perception, life experiences, and training. The pattern of study in which a person acquires education has a great influence on their personality. Objective To compare the personality traits and academic performance of boarders and non-boarders studying in a medical un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…When they were compared in terms of academic performance, day scholars were found to be better than their other counterparts. 13 A similar study conducted in India also showed better performance of day scholars academically. 14 Nayatanga and his colleagues conducted a study to compare the academic performance of hostelites and day scholars.…”
Section: Discussionmentioning
confidence: 75%
“…When they were compared in terms of academic performance, day scholars were found to be better than their other counterparts. 13 A similar study conducted in India also showed better performance of day scholars academically. 14 Nayatanga and his colleagues conducted a study to compare the academic performance of hostelites and day scholars.…”
Section: Discussionmentioning
confidence: 75%
“…An example of this is the study conducted by Khurshid et al 24 . A study in India and another by Dambudzu concluded that nonboarders were performing better academically when compared to nonboarders 25,26 . A study in Kenya found the lack of parental contribution and support to be a major factor in the poor performance of boarders as compared to non-boarders [27][28][29] .…”
Section: Discussionmentioning
confidence: 97%
“…22 Rehman K et al reported no difference of academic performance in medical professional exam but day scholars were found to be better than their other counterparts. 23,24 The country's education system needs to identify all the possible barriers while inculcating a change in the thinking style, research, deepening critical thinking, and also a change in teachers' attitudes toward curriculum designing (goals, objectives, learning content, instructional designs and evaluation methods); more so, it is suggested that proper attention should be paid to the need to develop and utilize critical thinking skills in the learners' education. 25 The current study results suggest that medical curriculum should be taught in an integrated manner to stimulate critical thinking skills among future healthcare providers.…”
Section: Discussionmentioning
confidence: 99%